Heparanase Overexpresses in Keratoconic Cornea and Tears Depending on the Pathologic Grade - García, Beatriz; García-Suárez, Olivia; Merayo-Lloves, Jesús; Ferrara, Guilherme; Alcalde, Ignacio; González, Javier; Lisa, Carlos; Alfonso, Jose F.; Vazquez, Fernando; Quirós, Luis M. (Disease Markers, 2017)
Background. Keratoconus has classically been defined as a noninflammatory disorder, although recent studies show elevated levels of inflammatory markers suggesting that keratoconus could be, at least in part, an inflammatory condition. Heparanase upregulation has been described in multiple inflammatory disorders. In this article, we study the differential expression of heparanase in cornea and tears from keratoconus patients and healthy controls. Methods. A transcriptomic approach was used employing quantitative polymerase chain reaction to analyze the expression of heparanase and heparanase 2 in stromal and epithelial corneal cells. The protein expression was analyzed by immunohistochemistry in corneal sections. Enzymatic activity in tears was measured using [3H]-labeled heparan sulfate as substrate. Results. Heparanase transcription was detected in stromal and epithelial cells and appeared upregulated in keratoconus. Overexpression of the enzyme was also detected by immunohistochemistry. Corneal expression of heparanase 2 was detected in some cases. Heparanase catalytic activity was found in tears and displayed a positive correlation with the degree of keratoconus. Conclusions. Heparanase overexpresses in keratoconic corneas, possibly reinforcing the inflammatory condition of the pathology. The presence of heparanase activity in tears allows us to propose its use as a biomarker for the diagnosis of the disorder.